Application of klauder wavelet for generation of synthetic seismic signals - Neelima, S; Saritha, A; S.Ramesh, K; Koteswara rao, S (International Journal of Engineering and Technology, 2018)
Analysis of reflected seismic waves gives the information about the earth and its inner core. This aids in monitoring earthquake, petroleum exploration, determination of the earth’s core structure, etc. Wavelet transforms is an efficient tool for analysis of seismic reflected signals. These transforms helps in complete extraction of the seismic signal buried in noise. In this paper an attempt is made to analyze a synthetic seismic signal by using Klauder wavelets.  The synthetic seismic signal is extracted by convoluting with the Klauder wavelet. Noise is completely removed as the wavelet spans a large spectrum of signals.